Investigation of novel carbazole-functionalized coumarin derivatives as organic luminescent materials. (December 2017) - Yu, Tianzhi; Zhu, Zeyang; Bao, Yanjun; Zhao, Yuling; Liu, Xiaoxiao; Zhang, Hui
Abstract: Four new carbazole-based coumarin derivatives comprising a carbazole core and one or two coumarin chromophores, 7-(diethylamino)-3-(4-(9-( p -tolyl)-9 H -carbazol-3-yl)phenyl)coumarin (Cz-Ph-C ) and 3, 3'-((9-( p -tolyl)-9 H -carbazole-3, 6-diyl)bis(4, 4′-phenyl))bis(7- (diethylamino)coumarin) (Cz-2(Ph-C) ), 7-(diethylamino)-3-(5-(9-( p -tolyl)-9H-carbazol-3- yl)thiophen-2-yl)coumarin (Cz-Th-C ) and 3, 3'-((9-( p -tolyl)-9 H -carbazole-3, 6-diyl)bis(thiophene- 5, 2-diyl))bis(7-(diethylamino)coumarin) (Cz-2(Th-C) ), were successfully synthesized as the emissive materials for organic light-emitting devices. The photophysical, electrochemical properties and thermal stabilities of the compounds were systematically investigated. The results showed that these coumarin-carbazole hybrids exhibited excellent thermal stabilities and high photoluminescence quantum efficiencies in dichloromethane solutions, and they emitted strong green emissions. The vacuum-processed doped devices with a configuration of ITO/TAPC (20 nm)/TBADN: Coumarin-carbazole hybrid (x wt%, 30 nm)/TPBi (50 nm)/Liq (2 nm)/Al (150 nm) was fabricated, in which the devices based onCz-Ph-C exhibited the best electroluminescence performance with a maximum brightness of 12910 cd/m 2 and a maximum luminous efficiencies of 7.39 cd/A and a maximum external quantum efficiency (EQE) of 3.36%. Graphical abstract: Four new carbazole-coumarin hybrids (Cz-Ph-C, Cz-2(Ph-C), Cz-Th-C andCz-2(Th-C) ) were successfully synthesized as the emissive materials for organic light-emitting devices. The vacuum-processed doped devices were fabricated. The devices withCz-Ph-C (10 wt%) displayed the best performance with a maximum brightness of 12910 cd/m 2 and a maximum luminous efficiencies of 7.39 cd/A and a maximum external quantum efficiency (EQE) of 3.36%. Highlights: Four carbazole-coumarin hybrids were synthesized for organic light-emitting devices. The hybrids exhibited strong green emissions in CH2 Cl2 solutions. The device based on the phenyl-bridged mono-coumarin hybrid displayed the best performance.